2011
DOI: 10.1159/000334983
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Validity of the Cornell Scale and the MADRS in Detecting Depression among Memory Clinic Patients

Abstract: Background: The aim of the study was to compare the validity of the Cornell Scale for Depression in Dementia (CSDD) and the Montgomery-Aasberg Depression Rating Scale (MADRS) among memory clinic patients. Methods: The scales were independently completed for 125 patients. The diagnosis of depression was made by psychiatrists blinded to the depression scores. Results: The mean score of the Mini-Mental State Examination was 25.5 (SD: 4.6), of the CSDD 6.8 (SD: 4.9), and of the MADRS 8.5 (SD: 6.8). In receiver ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 73 publications
(50 reference statements)
1
53
2
Order By: Relevance
“…The mean score of the MADRS was 9.7 (SD: 6.7), and 318 (61.2%) had a sum score of 7 and above. According to our previous validity study among the same group of patients, these cutoff points had the best sensitivity and specificity, and were therefore the most suitable for the present study [12]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean score of the MADRS was 9.7 (SD: 6.7), and 318 (61.2%) had a sum score of 7 and above. According to our previous validity study among the same group of patients, these cutoff points had the best sensitivity and specificity, and were therefore the most suitable for the present study [12]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous validation study using data from daily clinical practice, we filled in the two scales independently of each other, using two different sources of information (caregivers and patients). The correlation between the results of the two scales in that study was Spearman's rho = 0.43 [12]. A similar study, in a memory clinic in Brazil using the same methodology, also found a low correlation between the two scales of 0.46 [13].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations